Nursing Interventions And Pharmacological Treatments For Acute Glaucoma In Emergency Settings: A Narrative Review (The Review of Diabetic Studies, 2024)
Background: Acute angle-closure glaucoma (AACG) is an ophthalmic emergency characterized by a sudden, painful elevation of intraocular pressure (IOP) that can lead to irreversible optic nerve damage and vision loss within hours if not promptly treated. Effective management in the emergency department (ED) is critical to prevent permanent visual impairment.Aim: This narrative review aims to synthesize current evidence on the efficacy of combined nursing interventions and pharmacological treatments for AACG in emergency settings, evaluating their roles in rapid IOP reduction, patient stabilization, and preparation for definitive therapy.Methods: A comprehensive literature search was conducted across PubMed, CINAHL, and Cochrane Library databases (2010-2024). Included were clinical trials, observational studies, systematic reviews, and clinical guidelines. Data were extracted and narratively synthesized focusing on interdisciplinary emergency care pathways.Results: Evidence supports a synergistic approach. Immediate first-line pharmacological therapy (e.g., topical beta-blockers, alpha-2 agonists, systemic carbonic anhydrase inhibitors, and hyperosmotic agents) is foundational. Concurrently, structured nursing interventions—including rapid triage, pain and anxiety management, patient positioning, meticulous medication administration, and preoperative preparation—significantly enhance treatment efficacy, improve patient outcomes, and reduce time-to-definitive care.Conclusion: Optimal management of AACG in the ED requires a tightly integrated, protocol-driven partnership between emergency clinicians and nursing staff. Combining rapid, stepped pharmacological therapy with dedicated, knowledgeable nursing care is essential for successful emergency intervention and preservation of vision. Standardized, interdisciplinary protocols are recommended for all emergency settings.